Efektifitas Penambahan Ekstrak Buah Mengkudu (Morinda cirtifolia) Pada Pakan Terhadap Tingkat Kanibalisme dan Kelangsungan Hidup Ikan Beong (Hemibagrus nemurus) - Waluyo, Waluyo; Mujtahidah, Tholibah; Dzulqarnain, Muammar (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2024)
Beong fish is a sort of freshwater fish that is economically valuable and in high demand among the general populace. The high level of cannibalism at the seed stage reduces this fish's productivity. As a result, efforts are needed to domesticate beong fish utilizing therapies that can prevent cannibalism, such as noni fruit extract. Noni fruit contains scopoletin, which helps to increase serotonin levels in the brain, reducing aggression. The purpose of this study was to test how noni fruit extract reduced cannibalism in beong fish seeds (Hemibagrus nemurus). This study used a completely randomized design (CRD), with four treatments and three replications. The treatments that will be delivered are not fruit extracts. Treatment 1 contains 0 ml/l of noni extract; Treatment 2 contains 5 ml/l of noni extract; Treatment 3 contains 10 ml/l of noni extract; and Treatment 4 contains 15 ml/l of noni extract. The following characteristics were observed and analyzed: cannibalism level, survival, cannibalism type, fish behavior, and water quality. The study found that giving noni fruit extract reduced cannibalism in beong fish seeds. The optimal noni extract level is 11.18 ml/l to minimize cannibalism and maximize the survival of beong fish seeds. When using noni extract to soak beong fish feed in the form of tubifex worms, it is recommended to use an optimal noni extract concentration of 11.18 ml/l to maximize the utilization of the scopoletin compound in the noni extract in the fish's body and reduce cannibalism of beong fish seeds.